Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3177/jnsv.65.52
|View full text |Cite
|
Sign up to set email alerts
|

The Dietary Intake and Its Features across Four Seasons in the Metropolis of China

Abstract: Chinese diet pattern known as plant-based is more linked with seasonal supply, but it is lack of study on seasonal difference in dietary intakes in China. Our study was to assess seasonal variation in the absolute dietary intake among general population in a metropolis, Shanghai, China. A representative sample of general population aged 15 and older (n51,704) were randomly stratified-sampled from communities in Shanghai. Dietary survey included consecutive 3-day-24-hour diet record recall and household condime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
(78 reference statements)
3
6
0
Order By: Relevance
“…On the other hand, a dietary survey using FFQg [ 36 ] (a food frequency questionnaire based on food groups) administered to Japanese, Polish, and Thai individuals by Morinaka et al did not show seasonal changes [ 19 ]. However, in a report from the Netherlands and Spain [ 10 , 11 ] using dietary records and a study using 24-h recall [ 37 , 38 ], food and energy intake in winter were clearly higher than those in summer, and the reduction in energy intake in summer was consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, a dietary survey using FFQg [ 36 ] (a food frequency questionnaire based on food groups) administered to Japanese, Polish, and Thai individuals by Morinaka et al did not show seasonal changes [ 19 ]. However, in a report from the Netherlands and Spain [ 10 , 11 ] using dietary records and a study using 24-h recall [ 37 , 38 ], food and energy intake in winter were clearly higher than those in summer, and the reduction in energy intake in summer was consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…The median total protein and animal protein intake of the subjects were 80.1 g/d and 38.9 g/d. The protein intake exceeded protein RNI in 62.3% of the subjects, consistent with recent other population data from the Shanghai survey [22]. The positive rate of TPO-Ab, TG-Ab, and TR-Ab was 10.40%, 9.43%, and 8.47%, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Previous research on the seasonality of F&Vs in LMICs has largely been limited to rural areas, with intake of F&Vs tending to be higher during rainy/monsoon season compared with the dry/postmonsoon or winter season (19, 20), though not in all studies (21). Two recent studies in Shanghai, China, found that intake of F&Vs was highest in the summer, with particularly striking differences for fruits (22, 23). In contrast, a study in Ethiopia found little seasonal variability in intake of F&Vs in urban areas (24).…”
mentioning
confidence: 97%